Hitler's stormtroopers and the attack on the German Republic : 1919 - 1933 - Mitchell, Otis C. 1935- (McFarland, 2008)
"This book concentrates particularly on the Nazi Party and its growth during the years of the Weimar Republic, examining the paramilitary presence in Germany and Bavaria after World War I. The book features several photographs captured from the Nazi Party's Central Publishing Facility in Munich and passed to the author in the late 1950s"--Provided on back cover.